Understanding of khiyar ru’yah on online shopping : study on Academy Contemporary of Islamic Studies (ACIS). / Cut Rosmawar Tengku Syarbini - Tengku Syarbini, Cut Rosmawar (2019)
The sophistication of technology and the rise of modern lifestyles have influenced the way we live. Various transactions have been conducted online including online shopping activities. Many of us have been involved in this activity and most of them have experienced problems during this sale and purchase contract. Therefore, the principle of khiyar is provided to give the contractor a choice of whether to proceed with the sale or not if they are satisfied with the contract. Therefore, this study was conducted to look at the level of understanding of the concept of khiyar especially Khiyar Ru’yah in online shopping. Khiyar Ru’yah is a choice given to the contractor whether or not to proceed with the contract after looking at the subject matter of the contract. This study was conducted on the students of the Diploma of Muamalat and the Diploma of Halal Management part 4, ACIS. The data were analyzed using qualitative and quantitative research design by giving a survey and questionnaire. This study found that many of the students still do not know about Khiyar Ru’yah. Hopefully, this study will help to shed some light on the students' level of understanding of this khiyar and provide suggestions for increasing their knowledge of Khiyar Ru’yah.